STRATEGIES TO INCREASE COMMUNITY COMPLIANCE IN PAYING ZAKAT THROUGH DIGITALIZATION - Aceng Abdul Hamid; Winda Dwi Yanthi (Ikatan Dosen Menulis, 2025)
Zakat is the main instrument in the Islamic economic system which plays an important role in the equitable distribution of social welfare. However, the level of public compliance in paying zakat is still a challenge, especially in the aspects of awareness and ease of access. This study aims to analyze strategies to increase public compliance in paying zakat through digitalization, by highlighting the factors that affect the use of zakat digital platforms. The research method used is a quantitative and qualitative approach through surveys to muzakki (zakat payers) and interviews with managers of zakat institutions and Islamic economic experts. The results of the study show that zakat digitization has a significant role in increasing community compliance, especially through ease of transactions, transparency of fund management, and increasing zakat literacy. The main factors that affect include trust in digital platforms, ease of use of applications, and education about zakat obligations. Therefore, more innovative strategies are needed, such as collaboration between the government, zakat institutions, and sharia fintech providers in increasing public accessibility and trust in the digital zakat system. The implications of this study are expected to provide recommendations for policy makers in optimizing the role of digitalization to increase zakat compliance to support the welfare of the people.